Engineered extracellular vesicles-like biomimetic nanoparticles as an emerging platform for targeted cancer therapy - Liu, Xinyi; Xiao, Chunxiu; Xiao, Kai (Journal of nanobiotechnology, 2023)
Nanotechnology offers the possibility of revolutionizing cancer theranostics in the new era of precision oncology. Extracellular vesicles (EVs)-like biomimetic nanoparticles (EBPs) have recently emerged as a promising platform for targeted cancer drug delivery. Compared with conventional synthetic vehicles, EBPs have several advantages, such as lower immunogenicity, longer circulation time, and better targeting capability. Studies on EBPs as cancer therapeutics are rapidly progressing from in vitro experiments to in vivo animal models and early-stage clinical trials. Here, we describe engineering strategies to further improve EBPs as effective anticancer drug carriers, including genetic manipulation of original cells, fusion with synthetic nanomaterials, and direct modification of EVs. These engineering approaches can improve the anticancer performance of EBPs, especially in terms of tumor targeting effectiveness, stealth property, drug loading capacity, and integration with other therapeutic modalities. Finally, the current obstacles and future perspectives of engineered EBPs as the next-generation delivery platform for anticancer drugs are discussed.